Analysis of Understanding of the Nature of Science (NOS) and Scientific Literacy among Pre-Service Biology Teachers at HKBP Nommensen University Pematangsiantar - Sirait, Gloria; Basten Barat, Welmar Olfan; Gunaria Siagian; Intan Sukmawati Siburian; Wikky Pramudya Jasa (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to examine the understanding of the Nature of Science (NOS) and scientific literacy among pre-service biology teachers at Universitas HKBP Nommensen Pematangsiantar. This study employed a descriptive mixed-method approach, integrating qualitative and quantitative data to provide a comprehensive profile of students' understanding of NOS and scientific literacy. The research employed a descriptive qualitative approach to assess NOS using the VNOS Form B instrument, and a descriptive quantitative approach to evaluate scientific literacy through a 10-item multiple-choice test. The participants consisted of seventh-semester students from the Biology Education Study Program, selected using purposive sampling. NOS data were analyzed interpretively, while scientific literacy data were analyzed using percentage-based achievement. The findings reveal that students’ understanding of NOS varies across different aspects. A high proportion of students demonstrated informed views on the tentative nature (88%) and empirical basis (76%) of science; however, 80% still exhibited naïve conceptions in distinguishing scientific theories from scientific laws. The aspects of scientific method, creativity, and subjectivity are classified within the transitional category. Meanwhile, scientific literacy is categorized as high, with an average score of 68.75%, indicating strengths in data interpretation (72%) but weaknesses in designing scientific investigations (54%). These findings emphasize the importance of strengthening inquiry-based learning and enhancing epistemological understanding in teacher education programs, while providing baseline evidence for improving the integration of NOS and scientific literacy in pre-service biology teacher education.